(untitled) (Third Sector Social Economic Review, 2026)
Risk perception is a key factor influencing investor behavior in financial markets. Credit default swap (CDS) premiums, which reflect a country’s risk level, can significantly impact investor confidence. Money market funds, known for their low risk and short-term nature, serve as alternative investment instruments for fund suppliers in financial markets. This study investigates the relationship between CDS premiums and money market funds using daily data from April 8, 2020, to April 8, 2025. The time series analysis was conducted in three stages. First, the Phillips–Perron and Augmented Dickey–Fuller (ADF) unit root tests were used to examine stationarity. Second, the Engle–Granger cointegration approach was applied to determine whether a long-term relationship exists between the variables. Third, a Granger causality test within the VAR model framework was performed to identify the direction of this relationship. The results show that the series become stationary after first differencing, there is a long-term relationship, and a unidirectional causality runs from CDS premiums to money market funds. These findings suggest that changes in CDS premiums, as indicators of country risk, have a partial but noticeable effect on money market funds.